QORAQALPOGʻISTON RESPUBLIKASI CHO’L HUDUDLARI UZUN SHOXLI QOʻNGʻIZLARINING Neoplocaederus scapularis (COLEOPTERA: CERAMBYCIDAE) BIOEKOLOGIK XUSUSIYATLARI - Duysengaliev, E.S.; Juginisov , T.I.; Isaeva , S.T (Actual problems and prospects of the study of the fauna, 2024)
Distribution and biology of some little-known species of Neoplocaederus Scapularis (Coleoptera:Cerambycidae) collected in the north-east of Karakalpakstan by Takhtakopirsky district bordering Beruniysky in the south, Ellikkalinsky in the east, Karaozaksky in the west, Moinaksky district in the north-west, with the Republic of Kazakhstan and Navoi region and new information on ecology is presented. New habitats for species considered pests or invasive species, such as Aeolesthes sarta (Solsky, 1871) and Neoplocaederus scapularis (Fischer von Waldheim, 1821). The list of taxa collected by the first author during many years of field research in Karakalpakstan, and photographs of little-known species from his collection, including some endemics, are given. In addition, there are high-quality photographs of some extremely rare species collected during our expedition, namely Xylotrechus (Xylotrechus) (Gebler, 1825), as well as images of their habitat.